Espacialização dos campos nativos na escarpa devoniana do Parque Nacional dos Campos Gerais, PR - Dalazoana, Karine (2010)
In the present, the ecosystems‟ fragmentation is considered one of the main causes of the biodiversity loss in natural environments. The remaining native grassland (Estepe Gramíneo-Lenhosa) in Parana State has been suffering hard human pressure, especially due to the expansion of activities as agriculture, animal production and forestation. The Campos Gerais National Park maintains an important portion of these natural grassland ecosystems relatively well conserved. Comprehending the functional organization of this landscape is fundamental for its management, in both ways, as in conservation as much as in restoring destroyed areas. Therefore, this study aims to characterize the special heterogeneity of the grassland matrix by the boundaries of the Campos Gerais National Park, to comprehend its spacial organization and its functional relations. Moreover, it has been made analysis of the landscape‟s composition and structure based on maps, describing the physical characteristics of the area, followed by floristic and vegetation structure researches. There were 481 fragments identified, 54.5% of the Devonian Scarp in the Park is by native grassland. There is a predominance of Stricto Sensu Grasslands (Dry Grasslands), followed by the Wet Grasslands besides the Rocky Grasslands. The floristic research showed high vegetal diversity, with many endemic, rare and endangered species. The sample sufficiency was fixed between 14 and 18 meters, depending on the environmental conditions of the fragment. The landscape appears to be low to moderate diverse, with an similarity distribution of fragments (E = 0.91), with a lack of dominance (DOM = 0.10). The shape indices and circularity and fractal dimension revealed fragments varying from isogeometrical to slight linear. The analyzes of proximity and neighborhood showed a favorable context to connectivity and to the biological flow of species, once a great portion of the grassland fragments (about 78.6%) having neighbors until 100 meters far. So, larger fragments are source areas while the smaller ones are ecological stepping-stones and those more linear perform as corridors. For the generalist species, the grassland fragments of the Campos Gerais National Park seems to be connected, otherwise, for the restrictive species it is necessary future studies. There is a high susceptibility of edge related to the water flow, specially the Wet Grasslands. Management of the grassland areas is necessary to promote its natural regeneration, guarantying the conservation of fauna and flora, minimizing the human pressures and its consequent reducing biodiversity.